(untitled) (Research, Society and Development, 2020)
The present work deals with some aspects of environmental education and the relevance of its insertion in higher education. To this end, the research aims to verify the perception of management academics at the Federal University of Western Pará, Campus Alenquer, with regard to environmental concepts, as well as, definition of garbage, collection processes, impacts on the environment, its destination, among others. The methodology was developed through bibliographic research and survey of primary data, questionnaires applied to academics, minutes before the performance of assessment tests, to ensure the participation of the maximum number of students. The results presented reinforce the need for environmental education in undergraduate courses, since students had difficulties in answering questions. Finally, the study emphasizes the main points related to the environmental theme and how they report to the university campus under study, since it proclaims the need for environmental preservation as maintenance for future generations. In this perspective, public policies combined with environmental education that encourage the collection practices suitable for garbage, are essential for environmental conservation.